Modeling the large runup along a narrow segment of the Kaikoura coast, New Zealand following the November 2016 tsunami from a potential landslide. (1st March 2019) - Heidarzadeh, Mohammad; Tappin, David R.; Ishibe, Takeo
Abstract: The 2016 Mw 7.8 Kaikoura earthquake and consequent tsunami have been controversial because of uncertainty over whether and where the plate interface ruptured and the incapability of the proposed source models to reproduce the near-field runup of 7 m. Existing models identify a wide range of locations for the interface rupture, from on land to offshore, and fail to reproduce runup of 7 m near Kaikoura. To generate the large tsunami peak in Kaikoura tide gauge record and the observed runup height, offshore seafloor movement is necessary, but the offshore extension of the plate-interface rupture and its type, either seismic rupture or a landslide, is uncertain. Here, we propose a submarine landslide in addition to the earthquake source, with the landslide delayed 10–20 min after the earthquake rupture. The landslide volume is 4.5–5.2 km 3, located within 173.7–174.3 o E (longitude) and 42.6–42.15 o S (latitude). Our proposed dual tsunami source successfully reproduces near-field tide gauge records as well as observed near-field runup height of 7 m. We showed that more accurate source models of earthquakes can be achieved by considering observed runup data through runup inversions in addition to waveform inversions.